The Use of the Consolidated Framework for Implementation Research to Understand Facilitators and Barriers to Sexually Transmitted Infection Screening in Primary Care. Issue 9 (2nd September 2022) - Ahmad, Fahd A.; Dickey, Viani; Tetteh, Emmanuel K.; Foraker, Randi; McKay, Virginia R.
Abstract : Structured interviews guided by the Consolidated Framework for Implementation Research allowed the identification of contextual factors influencing the provision of sexually transmitted infection screening, facilitating future implementation of a risk-based sexually transmitted infection screening program. Abstract : Background: Adolescents bear a disproportionate burden of sexually transmitted infections (STIs) and the sequelae of delayed treatment, yet STI screening is infrequently performed in pediatric primary care clinics with many of those at-risk not administered testing. This study aims to understand contextual factors influencing STI screening and testing among adolescents in pediatric primary care. Methods: We used the Consolidated Framework for Implementation Research (CFIR) as part of a stepwise approach to facilitate a deep understanding the pediatric primary care environment. We conducted semistructured interviews of physicians, nurses, and patient-parent dyads from 4 pediatric primary care practices in the St. Louis metropolitan area about STI screening practices and common concerns regarding STI screening. Qualitative analysis was conducted using a categorical coding technique informed by the CFIR followed by a thematic coding technique. Results: We interviewed 23 physicians/nurses and 12 patient-parent dyads. Individual-level barriers to STI screening and testing included wide variability in clinicians' practice patterns and their perception of STI risk in the patient population. Structural barriers included a lack of capacity to perform testing in clinic and time constraints during patient visits. Confidentiality issues also created significant barriers to screening and testing on both individual and structural levels. Adopting confidential methods for testing and educating providers on patients' recommendations for STI testing were discussed as ways to potentially improve STI care in pediatric patients. Conclusions: Our use of the CFIR facilitated a systematic approach to identify gaps in STI care for adolescents and identified opportunities to close those gaps. An integrated, systematic approach that enhances patient confidentiality and improves clinicians' knowledge could address gaps in STI care in pediatric primary care settings.